Influence of Inlets Morphology and Forcing Mechanisms on Water Exchange between Coastal Basins and the Sea: A Hindcast Study for a Mediterranean Lagoon - Irene Simonetti; Lorenzo Cappietti (Journal of Marine Science and Engineering, 2022)
A numerical model, validated with field measurements, was applied to comparatively reconstruct the hydrodynamics of a eutrophic coastal lagoon in a set of scenarios over the last two centuries. The effect of major morphological changes on the water exchange with the open sea and water residence time is evaluated. The results show that the number and morphology of the lagoon inlets are crucial in determining the volume of water exchanged with the sea, the water transport timescales, and the extent of poorly circulated stagnant areas with poor flushing potential, which are areas where anoxic crises might develop. When all the relevant forcing mechanisms on the hydrodynamics are considered, great variability of the water residence time is found in the different historical scenarios, with values varying between 83 and 305 days. The effect of anthropic actions on the system hydrodynamics was quantitatively evaluated, consolidating the background knowledge to support the present and future management of this environmental system.